Covalent immobilization of fibroblast-derived matrix on metallic stent for expeditious re-endothelialization - Bedair, Tarek M.; Min, Ii Jae; Park, Wooram; Park, Bang Ju; Joung, Yoon Ki; Han, Dong Keun (한국공업화학회, 2019)
Here, we demonstrate a fibroblast-derived extracellular matrix (FDM) immobilized cobalt-chromium (Co-Cr) alloy surface to accelerate re-endothelialization. The surface characterization results showed that FDM molecules with their protein components such as collagen I, fibronectin, and laminin, were covalently grafted to Co-Cr surface. The in vitro cells experiments exhibited the superiority of the FDM-immobilized surface to capture and proliferate of endothelial progenitor and human umbilical cord vein endothelial cells than control Co-Cr alloy. These results suggested that the immobilization of FDM on the stent surface by this facile procedure could be an efficient and promising strategy to get expeditious re-endothelialization. (C) 2018 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.